2011
DOI: 10.1080/10632921.2011.545725
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Experience in Context: Sense-Making the Arts

Abstract: Recent research on arts and cultural audiences has attempted to go beyond the traditional social science surveys that assess attitudes or attendance to capture an understanding of how audiences actually experience the arts and what benefits or impacts those experiences provide. The study reported here contributes to this growing body of research by presenting in-depth case studies of four individuals and their chosen cultural experiences at various times through their lives. The authors used Dervin's Sense-Mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The study reported here is part of a larger project that focuses on everyday encounters with works of art (Foreman‐Wernet and Dervin , , , , in press; Foreman‐Wernet et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…The study reported here is part of a larger project that focuses on everyday encounters with works of art (Foreman‐Wernet and Dervin , , , , in press; Foreman‐Wernet et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…The sense‐making approach created by Dervin () is a communications model that has been applied to information‐seeking and information‐use studies from various disciplines, including health (Genuis, ; Godbold, ), arts and culture (Foreman‐Wernet & Dervin, ), generational groups (Koh, ; Meyers, Fisher, & Marcoux, ), and virtual information environments such as microblogging and discussion groups (Godbold, ; Heverin & Zach, ). The sense‐making approach is firmly established as a theoretical framework for studies that are focused on understanding everyday‐life information seeking, including purposive (goal oriented) and nonpurposive information‐seeking behaviors (Spink & Cole, ).…”
Section: Overview Of Theoretical Approachesmentioning
confidence: 99%
“…The identity construct is woven throughout this desire, reflecting individuals' fundamental drive for acceptance and belonging. Thus, identity is a relational process that informs organizational membership, commitment, and sensemaking (Foreman-Wernet & Dervin, 2011). Given the multiplicity of identities each individual represents, relational development, maintenance, or dissolution contributes to identity relevance and salience.…”
Section: Systems Thinking As a Theoretical Interpretive Frameworkmentioning
confidence: 99%